Morbilidad neonatal asociada a diabetes gestacional en un centro perinatológico de Santa Fe (SigMe, 2023)
Gestational Diabetes (GD) is the most frequent metabolic alteration associated with pregnancy and the Child of a Gestational Diabetic Mother (CGDM) presents a greater probability of neonatal complications. The main objective of this work is to determine the prevalence of neonatal disorders in CGDM. We conducted this case-control study at the Perinatology Center of Santa Fe, from January 10th, 2017 to January 8th 2018. Population was made up of 254 patients: 127 newborns CGDM (cases) and 127 controls newborns CnDM (children of non-diabetic mothers). All newborns were examined by neonatologists and studied with color Doppler echocardiography. Neonatal complications were measured and compared in both groups. We observed: 1) Metabolic morbidity in exposed newborns: 25.9% vs 7.08%, OR: 4.6; 95%CI: 2.09-10.09), p
Keywords: Gestational Diabetes; Neonatal Morbidity; Congenital Defects